Las causas de la guerra de Corinto: un análisis tucidídeo - Fornis, César (Gerión. Revista de Historia Antigua, 2008)
The anonymous author of the Hellenica Oxyrhynchia applied the Thucydides´ method to the analysis of the causes of the Corinthian War, so the Persian gold distributed by Timocrates the Rhodian (aitia) was only the catalyst of the opposition to the Lacedaimonian imperialism on the part of some Greek states economically exhausted (alethestate prophasis). In this work we show the evolution and effects that the Spartan imperialism had in different ways and stages during the inter war period, anyway the resistance, first passive and then active, they moved.
Keywords: War; Immediate cause; Genuine cause; Imperialism; Resistance; Hellenica Oxyrhynchia